Evaluation Of The Follow-Up Of Children Of Childcare Age During The Covid-19 Pandemic In Primary Care - Silveira, Camila Rocha; de Camargo, Miria Elisabete Bairros (Seven Editora, 2023)
Introduction: Children were one of the most affected audiences during the pandemic by COVID-19, bringing several concerns of how such context may affect child development in the long and short term. Objective: To identify whether the pandemic by COVID-19 affected the follow-up of the comprehensive health assessment of children of childcare age and the overall development of this public in the context of Primary Health Care. Methodology: This research is characterized as a quantitative descriptive study. A population of 666 records of users from 0 to 24 months of age was analyzed. Results and discussion: Among the total sample, 473 children were present at the consultations and 193 were absent. Final considerations: It is necessary to carry out permanent education actions with health professionals, so that the teams can develop strategies for health promotion and effectiveness of continued care for the child and the family. It suggests that further studies be conducted to evaluate the impact of the pandemic by COVID-19 on child development. DOI: https://doi.org/10.56238/colleinternhealthscienv1-097